Effects of low level electromagnetic field exposure at 2.45 GHz on rat cornea. (April 2013) - Akar, Ayşegül; Karayiğit, M. Önder; Bolat, Durmuş; Gültiken, M. Erdem; Yarim, Murat; Castellani, Gastone
Abstract Purpose: To investigate the effects of low level electromagnetic field (low level-EMF) exposure, as frequently encountered in daily life, on the normal rat cornea using histological and stereological method. Methods: Twenty-two adult male Wistar rats were randomly divided into two groups: Study group (n = 11) and control group (n = 11). Rats in the study group were exposed to 2.45 GHz microwave (MW) radiation (11.96 ± 0.89 V/m), 0.25 W/kg specific absorption rate (SAR) for 2 hours each day for 21 days. The corneal thickness and the anterior epithelium corneal thickness were measured using two different methods. Results: Using the histological method, the mean corneal thicknesses in the control and study group were 278.9 ± 54.5 μm, and 272.4 ± 85.6 μm, respectively. There was no statistically significant difference between the groups (p > 0.05). The anterior corneal epithelium thickness was 28.1 ± 4.9 μm in the control group and 31.7 ± 5.5 μm in the study group. There were statistically differences between the groups with regard to the thickness of anterior epithelium (p < 0.05). In the measurement made by the stereological method, the percentage of the cornea occupied by anterior corneal epithelium was 15.94% in the control group and 17.9% in the study group. Despite the fact that there was a relation between increased anterior epithelial area (AEA) and radiation exposure, no statistically significant relationship in area fraction of each compartment was found between the control and study groups. Conclusions: Results of this preliminary study show that exposure to MW radiation might cause alterations in the rat cornea.